Performance assessment of irrigation water management in old lands of the Nile Delta of Egypt - El-Agha, Doaa E.; David, S.; Ghanem, A.M. (Springer, 2011)
This paper provides the methodology and results of a cross-scale diagnostic performance assessment program of the irrigation water management in the old lands of the Nile Delta of Egypt. The analysis was done at three levels; main canal level, branch canals level and on-farm level of the Meet Yazid command (82,740 ha) for the year 2008-2009 to highlight areas for improvement. At the main canal level the annual average percentage of irrigation water returning to drains and groundwater was 53% of the total water supplied. Since Meet Yazid lies at tail end of the delta, and there is groundwater salinity, opportunities for reuse are increasingly limited moving north to Lake Burullus. This would indicate opportunities for real water savings. The results of monthly relative water supply of the main canal indicated mismatch between demand and supply especially during the winter months, and when supply is low farmers do reuse drainage or groundwater. Also, the assessment of the three branch canals showed non-uniformity of water distribution and mismatch between demand and supply even when comparing improved and non-improved canals. At the on-farm level in paddy fields, the amount of irrigation flows to drains and saline sinks varied from 0.46 to 0.71 of inflow. In spite of these values of non-uniformity and low depleted fraction, the relative evapotranspiration (ratio of actual to potential) evaporation was uniformly high, indicating most crops of most farmers were not water stressed, which is also confirmed by the high yield values. The average values of productivity per unit water depleted by ETact were 1.04 and 1.05 kg/m 3 for rice and wheat fields, respectively, with yields of rice and wheat at 8 and 6 t per ha respectively. On farm and tertiary improvements alone will not yield real water savings, as excess water in the main canal and drains will continue to flow out of the system. Rather the focus should first be on supplies to the main canal, accompanied by more precise on farm and water delivery practices at branch and tertiary levels, and ensuring that environmental flows are met. There is an added advantage of focusing on this tail end region of Egypt that this response would lessen vulnerability to reuse of polluted and saline water.